Rhetorical Schemes in Barack Obama’s Winning Speech - Widiatmika, Putu Wahyu; Budiarsa, I Made; Sadia, I Gde (Humanis, 2020)
This study is aimed to identify the kinds, functions, and meanings of rhetorical schemes applied in Obama’s speech. The data of this study were taken by documentation method and note-taking technique from the winning speech delivered by Barack Obama on November, 4 th 2008 at Grant Park in Chicago. The video is uploaded by Marc Schulz on October, 19th 2012 in YouTube and its transcript is available on ABC news (internet). In addition, the data were analyzed descriptive qualitatively using Holman’s theory about rhetorical devices (1960). This study revealed that there are three schemes in rhetorical devices namely phonological, morphological, and syntactical applied by Barack Obama. Furthermore, two functions applied are to give vivid example and to emphasize points. The meanings from applied rhetorical schemes are constructed based on the reference Obama does in his speech towards socio-historical events in America.